Komitmen Organisasi dan Kepuasan Kerja terhadap Turnover Intention - Avinda Ainun Jariyah; Ika Korika Swasti (IPM2KPE, 2022)
This study aims to analyze the effect of organizational commitment and job satisfaction on turnover intention at CV. Her appointment. This research method is descriptive quantitative. The research data is in the form of primary data. The research population was taken from employees of CV. The number of appointments was 121 people, and the sample taken was 55 people, the determination of which was based on a proportional random sampling technique. In this study, the determination of the sample was based on the location of the shop where the research was conducted. The data collection technique is using a questionnaire. The research data analysis method is Partial Least Square. The results of the study show, a) organizational commitment has a negative effect on Turnover Intention as indicated by path coefficients with a value of -0.262, and t-statistics with a value of 2.021> 1.96, which means it is significant; b) job satisfaction has a negative effect on Turnover Intention as indicated by the path coefficients worth -0.266, and t-statistics worth 2.143>1.96, meaning it is significant. In conclusion, a high level of organizational commitment can make a real contribution in reducing the level of turnover intention in CV. Her appointment. Also, a high level of job satisfaction can make a real contribution in reducing the level of turnover intention in CV. Her appointment. Keywords: Job Satisfaction, Organizational Commitment, Turnover Intention